Higiene-Sanitasi sebagai Prediktor Keberadaan Bakteri Coliform pada Produk Depot Air Minum - Widiyatmoko, Erwan; Suswati, Enny; Prayitno, Hadi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Along with the development of technology and increasing activities, people prefer a more convenient and economical solution in meeting their drinking water needs, namely by consuming drinking water from drinking water depots. Contaminated drinking water can be a source of food-borne diseases with the consumption of the same microorganisms. Hygiene-sanitation of drinking water depots is an effort to control the risk factors for contamination from drinking water depots so that drinking water depot products are safe for consumption. This study aimed to analyze the relationship between hygiene-sanitation of drinking water depots and the presence of coliform bacteria in drinking water depot products. The design of this study was cross-sectional involving 80 drinking water depots in Jember Regency, which were selected using proportional sampling techniques. Data were collected by observation using the drinking water depot hygiene-sanitation observation sheet. Samples of drinking water depot products were taken by environmental sanitation personnel from each health center, then sent to the laboratory for examination of total coliform bacteria. The variables studied were hygiene-sanitation of drinking water depots and total coliform. Statistical analysis was carried out using the Chi-square test. The results showed that 84% of drinking water depots met the requirements for hygiene-sanitation. The p value was 0.000 so it was interpreted that there was a relationship between hygiene-sanitation of drinking water depots and the presence of coliform bacteria in drinking water depot products. Furthermore, it was concluded that hygiene-sanitation is a predictor of the presence of coliform bacteria in drinking water depot products.Keywords: hygiene sanitation; drinking water depot; coliform bacteria ABSTRAK Seiring dengan perkembangan teknologi dan aktivitas yang semakin tinggi, masyarakat lebih memilih solusi yang lebih nyaman dan ekonomis dalam memenuhi kebutuhan air minum, yaitu dengan mengonsumsi air minum dari depot air minum. Air minum yang terkontaminasi, dapat menjadi sumber penyakit yang ditularkan melalui makanan dengan konsumsi mikroorganisme yang sama. Higiene-sanitasi depot air minum adalah upaya untuk mengendalikan faktor risiko terjadinya kontaminasi dari depot air minum agar produk depot air minum aman untuk dikonsumsi. Penelitian ini bertujuan menganalisis hubungan antara higiene-sanitasi depot air minum dengan keberadaan bakteri coliform pada produk depot air minum. Rancangan penelitian ini adalah cross-sectional yang melibatkan 80 depot air minum di Kabupaten Jember, yang dipilih dengan teknik proportional sampling. Data diambil dengan cara observasi menggunakan lembar observasi higiene-sanitasi depot air minum. Sampel produk depot air minum diambil oleh tenaga sanitasi lingkungan masing-masing puskesmas, lalu dikirim ke laboratorium untuk dilakukan pemeriksaan total bakteri coliform. Variabel yang diteliti adalah higiene-sanitasi depot air minum dan total coliform. Analisis statistik dilakukan menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa 84% depot air minum yang memenuhi persyaratan untuk higiene-sanitasi. Nilai p adalah 0,000 sehingga diinterpretasikan bahwa ada hubungan antara higiene-sanitasi depot air minum dengan keberadaan bakteri coliform produk depot air minum. Selanjutnya disimpulkan bahwa higiene-sanitasi merupakan prediktor keberadaan bakteri coliform pada produk depot air minum.Kata kunci: higiene sanitasi; depot air minum; bakteri coliform